Evaluasi Penggunaan Website Universitas Janabadra Dengan Menggunakan Metode Usability Testing - MZ, Yumarlin (Universitas Janabadra, 2016)
Web-based public services has become an important part in supporting the success of a university, but from the web-based service is still a lot that was difficult to use and does not function properly. This study was conducted to evaluate whether Janabadra University website has had the acceptability criteria of usability testing. The study was conducted using a questionnaire as a research instrument. Questionnaires distributed research consisted of 19 questions grouped into five variables usability. Based on the data processing result that the mean score of overall usability testing to measure website usage Janabadra University Yogyakarta to Learnability aspects of 3.42, efficiency of 3.39, memorability of 3.32, an error of 3.66 and 3.27 for satisfaction by respondents. From these results indicate that the website of University of Yogyakarta Janabadara already Quite Easy to use, but there are still some things that need to be improved especially in terms of memorability for a typical animated images and aspects of Satisfaction in finding other equipment that support as share files and chat.Keyword : Evaluation, Usability testing , Website Universitas Janabadra